Structure, Microstructure, and Optical Properties of Tb Doped ZnO_x000D_ Nanorods - (:unkn) unknown (My University, 2020)
The rare-earth-doped Zinc Oxides (ZnO) are significant materials, especially in photodetector technology, for high detectionand high-speed optical communication. Here, important physical properties of Terbium-doped ZnO synthesized by thehydrothermal method were analyzed based on their concentration dependence. Structural behaviors of the nanorods wereidentified by the X-ray diffraction (XRD) technique and were figured out that Zn1-xTbxO samples were hexagonal Wurtzitestructure with no secondary phase. The results of the structural behaviors were also proved by Rietveld analysis. The effect ofTb element in Zn1-xTbxO composition was clarified by calculating lattice parameters and cell volumes. To define the systembetter, microstructural parameters were provided by calculation. Scanning Electron Microscope images revealed randomagglomeration. Due to the small amount of Tb increment in Zn1-xTbxO set, the desired elemental composition results wereobtained in the nanorod sets (from x=0 to x=0.05 with the increment x rate of 0.01). By plotting (??(???? ) ℎυ)2 versus hʋ, thebandgap energies of Zn1-xTbxO structures were determined, and the variation of Eg energies with increasing Tb dopant in thestructures were discussed.

Nadir toprak katkılı Çinko Oksitler (ZnO), fotodetektör teknolojisinde özellikle yüksek algılama ve yüksek hızlı optik iletişim_x000D_ için oldukça önemli malzemelerdir. Bu çalışmada, hidrotermal yöntemle sentezlenen Terbium katkılı ZnO'nun önemli fiziksel_x000D_ özellikleri, konsantrasyon bağımlılıklarına göre analiz edilmiştir. Nano çubukların yapısal davranışları, X-ışını kırınımı (XRD)_x000D_ tekniği ile tanımlanmış ve Zn1-xTbxO örneklerinin ikincil fazı olmayan altıgen Wurtzite yapı olduğu tespit edilmiştir. Yapısal_x000D_ davranışların sonuçları, Rietveld analiziylede kanıtlanmıştır. Tb elementinin Zn1-xTbxO bileşiğindeki etkisi, kafes parametreleri_x000D_ ve hücre hacimleri hesaplanarak saptanmıştır. Yapıyı daha iyi tanımlamak için hesaplama yoluyla mikroyapısal parametreler_x000D_ elde edilmiştir. Taramalı Elektron Mikroskobu görüntüleri rastgele dağılımı ortaya çıkarmıştır. Zn1-xTbxO setindeki az_x000D_ miktardaki Tb artışına bağlı olarak, nano çubuk setleri (x = 0' dan x = 0,05'e kadar olan artışlarla) oldukça iyi elementsel_x000D_ kompozisyon sonuçları vermiştir. (??(???? ) ℎυ)2 'ye karşılık hʋ'ye göre, Zn1-xTbxO yapılarının bant aralığı enerjileri belirlendi_x000D_ ve yapılardaki artan Tb dopantına bağlı Eg enerjilerinin değişimi tartışıldı.
Tb Katkılı ZnO Nanoçubukların Yapı, Mikroyapı ve Optik Özellikleri